Comprehensive analysis of amino acid profile in camel milk: Implications for nutrition and sustainable development - Kuanysh Syman; Raushangul Uazhanova; Zhulduz Suleimenova; Rakhmatova Markhabo Rasulovna; , Elnura Xamdamova; Kuryozov Urinboy Sabirovich; N. Esanmurodova; Rustem Shichiyakh; Sabirova Nadira Kamiljanovna; Nasirova Saodat Abdullayevna; Sullieva Suluv Khurramovna; Khushbok Bobonazarovich Narbutaev; et al. (Caspian Journal of Environmental Sciences)
Camel milk has emerged as a subject of scientific interest due to its potential nutritional value and suitability for arid regions. This investigation's purpose was to furnish a detailed and extensive examination of the amino acid profile in camel milk, exploring its nutritional value and implications for sustainable development. Fifty dromedary camels provided the milk samples that were collected across five geographical locations. Free and protein-bound amino acids were analyzed using high-performance liquid chromatography. In vitro protein digestibility assays were conducted. Results were compared with bovine and human milk samples. Statistical analyses included ANOVA, correlation analysis, and principal component analysis. Camel milk showed significantly higher levels of essential amino acids, particularly branched-chain amino acids, compared to bovine and human milk. Camel milk's branched-chain amino acid content was elevated by 23% over bovine milk and by 89% over human milk. Camel milk proteins exhibited superior in vitro digestibility (89.7% ± 2.3%) compared to bovine milk proteins (78.4% ± 1.9%). Subtle geographical variations in amino acid profiles were observed, with samples from the Arabian Peninsula showing slightly higher concentrations of most essential amino acids. The unique amino acid profile and high protein digestibility of camel milk suggest its potential as a valuable nutritional resource, particularly in arid regions facing environmental and nutritional challenges. These findings support the promotion of camel husbandry as a sustainable agricultural practice in challenging environments, aligning with global sustainable development goals.